2019
DOI: 10.1111/hex.12978
|View full text |Cite
|
Sign up to set email alerts
|

Getting underneath the skin: A community engagement event for optimal vitamin D status in an ‘easily overlooked’ group

Abstract: Background: Patient and public involvement and engagement (PPIE) is recognized asimportant for improved quality in health service provision and research. Vitamin D is one area where PPIE has potential to benefit public health initiatives, particularly for women and children with increased skin pigmentation (ie at high risk of deficiency) who are easily overlooked.Objective: We report findings from a community PPIE event that explored the knowledge, barriers and promoters for optimal vitamin D status amongst an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…There is a pressing need to study the knowledge, attitudes, and practices of the wider community, in particular from Black, Asian and minority ethnic subpopulations, to gain an understanding of the facilitators of and barriers to vitamin D supplementation in men, women, and children. Lee C et al explored these aspects in depth with a Somali community in Northwest London and found that a lack of awareness, access, and a reluctance to medicalise a natural state (pregnancy) were key issues [ 10 , 24 ]. The work undertaken included a systematic review that reported a paucity of studies that address the behavioural determinants that would help attain an adequate vitamin D status in hard-to-reach communities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a pressing need to study the knowledge, attitudes, and practices of the wider community, in particular from Black, Asian and minority ethnic subpopulations, to gain an understanding of the facilitators of and barriers to vitamin D supplementation in men, women, and children. Lee C et al explored these aspects in depth with a Somali community in Northwest London and found that a lack of awareness, access, and a reluctance to medicalise a natural state (pregnancy) were key issues [ 10 , 24 ]. The work undertaken included a systematic review that reported a paucity of studies that address the behavioural determinants that would help attain an adequate vitamin D status in hard-to-reach communities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We had planned to analyse behavioural interventions using HBM constructs (28) and the Behaviour Change Wheel framework criteria (30) . We have utilised HBM constructs for assessment in a previous patient and public involvement study (29) .…”
Section: Discussionmentioning
confidence: 99%
“…High-risk groups may need individualised advice and information on the need for vitamin D supplements. In addition, it may be important to address perceived medicalisation of vitamin D supplements, whereby women feel they only need to take a supplement on the recommendation or prescription from their GP (29) . Currently in the UK, patients and the public are advised to purchase vitamin D, unless eligible for the Healthy Start Scheme (19) .…”
Section: Behavioural Interventions For Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…London and found that a lack of awareness, access, and a reluctance to medicalise a natural state (pregnancy) were key issues (10,24). The work undertaken included a systematic review that reported a paucity of studies that address the behavioural determinants that would help attain an adequate vitamin D status in hard-to-reach communities (10).…”
Section: Lee C Et Al Explored These Aspects In Depth With a Somali Co...mentioning
confidence: 99%